A Preliminary Study on Vibration Response of Profiled Steel Sheet Dry Board (PSSDB) System under Heel-drop Test - Roslan, Aina Syafawati; A. Majid, Masni; Mohd Jaini, Zainorizuan; Ismail, Mohd Hanif; Sutiman, Nur Adidah (International Journal of Integrated Engineering, 2022)
This paper aims to evaluate the vibration response of the profiled steel sheet dry board (PSSDB) composite system under heel-drop test. Three (3) specimens with dimensions of 840mm width and 2000mm length were prepared. The specimen consists of a sample without concrete infill (P45HL), foamed concrete as infill (P45FC), and normal concrete as infill (P45NC) material. The specimen was erected using profiled steel sheet (PSS), 1mm thickness, and connected to a dry board (DB), 16mm thickness using self-drilling screws at 200mm screw spacing along the longitudinal direction. A heel-drop test was conducted, and modal analysis was performed using MEscope software. The FRF measurement was carried out using accelerometers, and the time-domain measured responses were converted to FRF to acquire modal characteristics such as natural frequency and mode shape of the structures. The natural frequency of the first mode shape is 17.7Hz, 14.2Hz, and 4.5Hz respectively for specimen P45H, P45FC, and P45NC. It demonstrates that the natural frequency of the specimen without infill and foamed concrete as infill is more than the human comfort limit value of 8Hz, implying that P45HL and P45FC will be comfortable for building occupants.